Development of IN-WAY GENORA Learning Media (Interactive Wayground Based Material for Recognizing Norms in Society) Elementary School - Nayla Mayzurra; Sukriadi Sukriadi; Taufik Hidayat; Iksam Iksam; Makmun Makmun (FKIP - Universitas Riau, 2026)
This research is motivated by the low level of student involvement in Pancasila Education learning, particularly in the topic of recognizing norms in society. This condition is influenced by teacher centered learning practices and the limited use of interactive and technology based learning media in the classroom. As a result, students tend to be passive and less motivated during the learning process. This study aims to develop IN-WAY GENORA learning media (Interactive Wayground based Material on Recognizing Norms in Society) and to determine its feasibility and practicality for sixth grade elementary school students. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through validation questionnaires completed by media experts, material experts, and language experts, as well as response questionnaires from teachers and students. The results indicate that the IN-WAY GENORA media achieved feasibility percentages of 91% from media experts, 91% from material experts, and 97% from language experts, all categorized as very feasible. Furthermore, student responses reached 86% and teacher responses reached 82%, both classified as very practical. These findings indicate that IN-WAY GENORA is highly suitable and practical for supporting Pancasila Education learning in elementary schools.